From Fragmented Training to Integrated Competency Development: A Spencer-Based Model for Medical Laboratory Technology Professionals in Primary Healthcare - Dewi Kunia; Afandi , Muhamad Nur; Rahman , Abdul; Abdullah, Sait (JURNAL MANAJEMEN MOTIVASI, 2026)
Laboratory services are essential for accurate diagnosis and effective public health action, requiring competent and standardized Medical Laboratory Technology Professionals (ATLM). This qualitative study examined competency development among ATLM personnel at 15 Community Health Centers under the Sukabumi City Health Office and developed an integrated competency model. Data were collected through interviews, observations, document review, and focus group discussions, and analyzed using the Miles and Huberman interactive model with triangulation. Findings revealed strong professional attitudes and motivation but deficiencies in technical skills, quality assurance, laboratory management, and certification. An evidence-based, context-specific competency model is proposed to enhance laboratory quality and public health outcomes.